Accumulation of trace elements in sediment and fish species of Paira River, Bangladesh - Md. Saiful Islam; Md. Habibullah-Al-Mamun (AIMS Environmental Science, 2017)
Sediments and tissues of eleven fish species (Channa punctata, Cyprinus carpio, Heteropneustes fossilis, Colisa fasciata, Channa striata, Notopterus notopterus, Tenualosa ilisha and Corica soborna) were analyzed for (chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd) and lead (Pb)). The abundance of trace elements in sediments were Cr > Ni > Cu > Pb > As > Cd and in fish species were Cu > Ni > Cr > Pb > As > Cd. The range of mean element concentration in fish species were Cr (0.44–0.97), Ni (0.45–1.1), Cu (0.91–1.5), As (0.18–0.37), Cd (0.016–0.20) and Pb (0.47–0.92 mg/kg wet weight (ww)). The concentrations of Ni, Cd and Pb in some fish species exceeded the international permissible standards suggesting that these species are not safe for human consumption. The biota-sediment accumulation factor for the studied elements in C. soborna and T. ilisha were slightly higher than the other species indicated that these species can be used as a potential bio-indicator for the contamination study of trace elements.